A pluralidade poética de Mário Jorge : do concretismo a outras expressões poéticas - Mendonça, Katherine de Albuquerque (2023)
This research is focused on the study of the works of the writer, Mário Jorge, from Sergipe, as far as it intends to investigate his poetic process through the books: Revolição (1968), Cuidado, silêncios soltos (1993), De repente, há urgência (1997) e A noite que nos habita (2003), Through this path of scrutinizing the aesthetic and discursive resources of Mariojorgian poems, the presence of concretist aspects in the poet's production is advocated, also reaching the understanding of recognizing him as a disseminator of Concretism in Sergipe. Thus, the studies carried out by the Campos brothers and by Décio Pignatari based on the concrete poetry theory (1975) guide the research in this direction, verifying the threedimensional plane of reading – word, sound and image. Additionally, the issues of the Counterculture movements investigated by Maciel (1973) serve as a basis for understanding the political and critical content present in Mário Jorge's creations, considering that his productions are also known for their strong tendency towards criticism and protest. Another foundation for this research is the one developed by Genette (2009) about editorial paratexts, that is, what goes beyond the written text in editions of the works, with the intention of allowing the reader to access other information about the author and his works. From the perspective of Sant'Anna (1997), regarding the relationship between poetry and ideology, the approximation between the poetry of Mário Jorge and the ascending artistic movements in the sixties, a social and political content is formulated aligned with an aesthetic elaboration of language that spark the dialogue with the literary movements of the time. Making this perspective an object of study is to rethink the existence of Mário Jorge in the Brazilian literature scenario, proposing a critical analysis angle that goes beyond defining it as a category of local literature. In this way, the emphasis that is given to the concretist movement is a pathway, especially when Mário Jorge is considered a restless writer: he spreads Concretism and is, at the same time, articulated by other poetic dictions.